PEDOT: PSS promotes neurogenic commitment of neural crest-derived stem cells - Pisciotta, Alessandra; Lunghi, Alice; Bertani, Giulia; Di Tinco, Rosanna; Bertoni, Laura; Orlandi, Giulia; Biscarini, Fabio; Bianchi, Michele; Carnevale, Gianluca (Frontiers in Physiology, 2022)
Poly (3,4-ethylendioxythiophene) polystyrene sulphonate (PEDOT:PSS) is the workhorse of organic bioelectronics and is steadily gaining interest also in tissue engineering due to the opportunity to endow traditional biomaterials for scaffolds with conductive properties. Biomaterials capable of promoting neural stem cell differentiation by application of suitable electrical stimulation protocols are highly desirable in neural tissue engineering. In this study, we evaluated the adhesion, proliferation, maintenance of neural crest stemness markers and neurogenic commitment of neural crest-derived human dental pulp stem cells (hDPSCs) cultured on PEDOT:PSS nanostructured thin films deposited either by spin coating (SC-PEDOT) or by electropolymerization (ED-PEDOT). In addition, we evaluated the immunomodulatory properties of hDPSCs on PEDOT:PSS by investigating the expression and maintenance of the Fas ligand (FasL). We found that both SC-PEDOT and ED-PEDOT thin films supported hDPSCs adhesion and proliferation; however, the number of cells on the ED-PEDOT after 1 week of culture was significantly higher than that on SC-PEDOT. To be noted, both PEDOT:PSS films did not affect the stemness phenotype of hDPSCs, as indicated by the maintenance of the neural crest markers Nestin and SOX10. Interestingly, neurogenic induction was clearly promoted on ED-PEDOT, as indicated by the strong expression of MAP-2 and β—Tubulin-III as well as evident cytoskeletal reorganisation and appreciable morphology shift towards a neuronal-like shape. In addition, strong FasL expression was detected on both undifferentiated or undergoing neurogenic commitment hDPSCs, suggesting that ED-PEDOT supports the expression and maintenance of FasL under both expansion and differentiation conditions.